Some concerns regarding the CAT16 chromatic adaptation transform. Issue 1 (18th November 2019) - Smet, Kevin A. G.; Ma, Shining
Abstract: In recent literature, a new chromatic adaptation transform, CAT16, has been published to improve upon the widely used CAT02 model. The CAT16 model is based on the form of the CAT02 transform adopted in CIECAM02, but uses a slightly different sensor space to fix some gamut problems plaguing CIECAM02 and adopts a two‐step CAT to ensure symmetry and transitivity. CAT16 is included in CAM16 but is also being promoted as a stand‐alone CAT, one that can be used outside of the CAM16 model. However, the use of CAT16 as a stand‐alone model can cause inconsistencies in the calculated corresponding colors due to the presence of the relative luminance of the adapting white ( Y w ) in the von Kries‐Ives gain control factors. Such inconsistencies are not present for the stand‐alone version of the CAT02 model, which, unlike the version adopted in CIECAM02, does not include the Y w factors. CAT16 should therefore be modified by omitting the Y w factors. In this article, we will briefly discuss these issues in more detail and provide a consistent two‐step CAT adopting the CAT16 sensor space.